SDH Subunit Mutation Status in Saliva: Genetic Testing in Patients with Pheochromocytoma - Osinga, T. E.; Xekouki, P.; Nambuba, J.; Faucz, F. R.; de la Luz Sierra, M.; Links, T. P.; Kema, I. P.; Adams, K.; Stratakis, C. A.; van der Horst-Schrivers, A. N. A.; Pacak, K. (Hormone and Metabolic Research, 2016)
Germline mutations occur in up to 30–40% of pheochromocytoma/paraganglioma, with mutations in the succinate dehydrogenase (SDH) subunits B (SDHB) and D (SDHD) being the most common. Blood samples are favored for obtaining high quality DNA, however, leukocytes can also be obtained by collecting saliva. The aim of this study was to determine whether SDHB and SDHD gene mutations in patients with pheochromocytoma/paraganglioma could be determined using a salivary sample. Paired blood and salivary samples were collected from 30 patients: 9 SDHB mutation positive, 13 with a SDHD mutation, and 8 without any SDHx mutations. The Oragene DISCOVER kit was used to collect and extract DNA from saliva. Blood DNA was extracted from EDTA blood samples. The DNA purification and concentration were measured by spectrophotometry. The 8 exons of SDHB and the 4 exons of SDHD were amplified and sequenced by PCR-based bidirectional Sanger sequencing. Total DNA yields from blood DNA were similar to those obtained from saliva DNA [mean (±SD) saliva vs. blood DNA concentration 514.6 (±580.8) ng/µl vs. 360.9 (±262.7) ng/µl; p=0.2)]. The purity of the saliva DNA samples was lower than that of blood [mean OD260/OD280 ratio 1.78 (±0.13) vs. 1.87 (±0.04); p=0.001, respectively], indicating more protein contamination in the saliva-extracted DNA. This study shows that salivary DNA collected from patients with pheochromocytoma/paraganglioma is a good alternative for extraction of genomic DNA for its high DNA concentration and acceptable purity and can be used as an alternative to blood derived DNA in screening for SDHB and SDHD mutations.
Keywords: SDHx mutations; pheochromocytoma; paraganglioma; DNA; saliva